1996
DOI: 10.1002/(sici)1099-114x(199607)20:7<581::aid-er168>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of tergitol-7 in photogalvanic cell for solar energy conversion and storage: Toluidine blue‐glucose system

Abstract: Photogalvanic effects were studied in a photogalvanic cell containing toluidine blue, glucose and tergitol-7 as a photosensitizer, reductant and surfactant, respectively. The photocurrent and photopotential generated by this system were 70 pA and 315 mV, respectively. The effects of different parameters on the electrical output of the cell were observed. Current/voltage characteristics of the cell have also been studied, and a mechanism has been proposed for the generation of photocurrent in photogalvanic cell. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Later on, Kaneko and Yamada (1977), Murthy et al (1980), Rohatgi Mukherjee et al (1983, Ameta et al (1989aAmeta et al ( , 1989b, and Gangotri et al (1996 reported some interesting photogalvanic systems. Theoretical conversion efficiency of photogalvanic cells is about 18%, but the observed conversion efficiencies are quite low due to lower stability of dyes, back-electron transfer, aggregation of the dye molecules around electrode, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Kaneko and Yamada (1977), Murthy et al (1980), Rohatgi Mukherjee et al (1983, Ameta et al (1989aAmeta et al ( , 1989b, and Gangotri et al (1996 reported some interesting photogalvanic systems. Theoretical conversion efficiency of photogalvanic cells is about 18%, but the observed conversion efficiencies are quite low due to lower stability of dyes, back-electron transfer, aggregation of the dye molecules around electrode, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ameta et al [9] have studied the use of micelles in photogalvanic cell for solar energy conversion and storage. Gangotri et al [10,11] have increased the electrical output as well as storage capacity up to reasonable mark by using various photosensitizer with micelles in photogalvanic cell. Some more phenothiazine dyes like Azur-B, toludine blue, and methylene blue etc.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Ameta et al (1958), Kaneko and Yamada (1977), Murthy and Reddy (1983), Murthy et al (1980), Rohatgi-Mukherjee et al (1983), and Gangotri et al (1996) reported some interesting photogalvanic systems. Hoffman and Lichtin (1979) have discussed various problems encountered in the development of this field.…”
Section: Introductionmentioning
confidence: 98%